Do fiscal regimes matter for fiscal sustainability in South Africa? A Markov-switching approach - Gabriel Temesgen Woldu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper empirically examines South Africa's fiscal sustainability through a Markovswitching model which utilizes quarterly datasets for the period from 1960 to 2019. The results show that public debt responds positively, demonstrating a sustainable fiscal policy. Furthermore, considering the regime-specific feedback coefficients of the fiscal policy rule and the durations of fiscal regimes, the study finds that South Africa's fiscal policy satisfies the No-Ponzi game condition. Therefore, from a policy perspective, the South African government should take measures such as pension reforms, reducing operational expenses, reducing subsidies, and funding micro and small enterprises to gain the double dividend on the expenditure side along with revenue-enhancing measures on consumption taxes to achieve stable public finances and lower debt levels.
Keywords: E62; F34; H62; 330; fiscal sustainability; Markov-switching model; South Africa